FAKTOR YANG MEMPENGARUHI PENGETAHUAN REMAJA DALAM PENCEGAHAN HIV AIDS DI SMA N 7 KOTA PEKANBARU TAHUN 2018 - Dona Martilova (LPPM Universitas Abdurrab, 2020)
Acquired Immune Deficiency Syndrome (AIDS) attracted the attention of the health community for the first time in 1981 after the discovery of cases such as Pneumocystis Carinii Pneumonia and Kaposi's Sarcoma. After going through the research process it turns out that HIV (Human Immunodeficiency Virus) is the virus that causes these cases. HIV is a group of Retroviruses that attack the human immune system, while the collection of certain clinical conditions that are the end result of HIV infection is called AIDS (Acquired Immune Deficiency Syndrome) (S.A. Price, 2006). According to (BKKBN, 2010), approximately 50% of people with AIDS in Indonesia are adolescent age groups. During adolescence often arises a sense of wanting to try this is important for adolescent reproductive health. Behavior of wanting to try new things if encouraged by sexual stimulation can bring adolescents into premarital sex with one of the consequences of transmission of venereal diseases including HIV / AIDS (Kumalasari, I, Andhyantoro, 2012). The purpose of this study was to determine the factors that influence adolescent knowledge in preventing HIV and AIDS in SMA N 7 Pekanbaru City. This research is an analytic research with Cross Sectional approach where the independent variables are Age, Attitude, Source of Information while the dependent variable is Youth Knowledge. The sampling technique was stratified with 83 respondents. The results of the study were calculated using the Chi Square statistical test results with a value of α 5% obtained results Age (p value 0.017 and OR 3.4), Attitude (p value 0.003 and OR 4.3), Information Sources (p values ​​0, 003 and OR 3.9) . Then Ho is rejected and Ha is accepted where there is a relationship between Age, Attitude, source of information with Youth Knowledge in HIV AIDS prevention. It is necessary to increase health promotion by involving cross-sectors to the community, especially school adolescents by providing counseling about HIV AIDS, including prevention of sexually transmitted diseases in order to reduce the transmission of HIV AIDS